Unlocking Competitive Talent: a Case Study on the Improvement of Leadership Development Through a Learning Journey (Catalyser Program) at PT Pertamina - el Mubarak, Muhammad Fahmi; Lantu, Donald Crestofel (Riviera Publishing, 2025)
This study critically evaluates the Catalyser Leadership Development Program implemented by PT.Pertamina (Persero), Indonesia's state-owned energy giant, against the backdrop of accelerating global energy transitions and organizational restructuring. Through in-depth interviews with 3 key stakeholders (program alumni, non alumni, and HR Designer), the research reveals a paradox: while the program successfully employs blended learning methodologies aligned with 70:20:10 principles (Lombardo & Eichinger, 1996), critical disconnects emerge in sustaining leadership capabilities post-program. The study makes a significant contribution by proposing an enhanced